PENGARUH KETERAMPILAN DASAR MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI DI SMA NEGERI 1 PANGARIBUAN PROVINSI SUMATERA UTARA - Novri Fiantry Sinaga; Sri Kartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrac:This study aims to determine the effect of basic teaching skills of teachers to wards students’ learning outcomes on accounting subject at the public high school 1 Pangaribuan Province of North Sumatera. Populasi of the research is student, grade XI IPS a much of 120; sample is gained using simple random sampling technique, resulted 55 respondents. Data then is analysed using SPSS version 16. The result showed that the basic teaching skills of teachers has significant effect on student learning outcomes, 57.6%. The more often teachers teach basic skills performed by teachers expected the higher the students learning outcomes. Simple linier regression equation obtained in this study is Y = 39,547 + 0,494 X. This means that if the teachers to teach basic skills (x) does not exist, the amount of learning outcomes (y) of 39,574 and of any increase in the teachers teaching basic skills will improve student learning outcomes at 0,494.Key Words: Teaching basic skills teachers and learning outcomes